2013
DOI: 10.1021/nl4026902
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and Controllable Flame Reduction of TiO2 Nanowires for Enhanced Solar Water-Splitting

Abstract: We report a new flame reduction method to generate controllable amount of oxygen vacancies in TiO2 nanowires that leads to nearly three times improvement in the photoelectrochemical (PEC) water-splitting performance. The flame reduction method has unique advantages of a high temperature (>1000 °C), ultrafast heating rate, tunable reduction environment, and open-atmosphere operation, so it enables rapid formation of oxygen vacancies (less than one minute) without damaging the nanowire morphology and crystallini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
137
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(152 citation statements)
references
References 38 publications
(74 reference statements)
8
137
0
Order By: Relevance
“…Flame annealing method is reported by Zheng's group [87][88][89][90]. The as-deposited TiO 2 nanotube, Fe 2 O 3 nanorod, and so on undergo a fast annealing treatment to realize high crystallinity [87,90].…”
Section: Other Film Deposition Methodsmentioning
confidence: 99%
“…Flame annealing method is reported by Zheng's group [87][88][89][90]. The as-deposited TiO 2 nanotube, Fe 2 O 3 nanorod, and so on undergo a fast annealing treatment to realize high crystallinity [87,90].…”
Section: Other Film Deposition Methodsmentioning
confidence: 99%
“…Reported hematite at band potentials range between 0.4 and 0.6 V vs. RHE and thus our values coincide with these. 54,56,68 Aer the Ti treatment the MS plots become more at (Fig. 6Sb †) indicating an increase in donor density, however, extracting the at band potentials and the donor densities quantitatively is not possible.…”
Section: Mott-schottky (Ms) and Electrochemical Impedance Spectroscopmentioning
confidence: 99%
“…H 2 O 2 is used as a probe molecule to evaluate the efficiency and the kinetic limitations of the different photoanodes as the oxidation of H 2 O 2 is kinetically much easier than water oxidation. 55,56 We performed photoelectrochemical experiments in the presence of 0.5 M H 2 O 2 ( Fig. 4Sa and b †).…”
mentioning
confidence: 99%
“…35 The C-doped TiO 2 shifted the level of the valence band, resulting smaller bandgap energy. Yang et al and Li et al reported independently the fabrication of Sn-doped Fe 2 O 3 nanostructure on the FTO glass for decreasing electron-hole recombination.…”
Section: Surface Engineering Routes For Metal Oxide Nanostructurementioning
confidence: 99%